Defender of Democracy: The Role of Indonesian Constitutional Court in Preventing Rapid Democratic Backsliding - Adfin Rochmad Baidhowah (Constitutional Review, 2021)
Debate on the quality and durability of Indonesia’s democracy has intensified in recent years. Political scholars had generally praised the country’s democratic achievements and stability in the two decades following the 1998 resignation of long-serving president Suharto. But more recently, a growing number of academics have noted that elements of Indonesia’s democracy are being eroded. While the issue of Indonesia’s democratic backsliding has gained considerable attention and generated much academic literature, few scholars have analyzed why Indonesia has not entered a phase of rapid backsliding or a return to authoritarianism. This article argues the role of the Indonesian Constitutional Court in the consolidation of democracy has been frequently overlooked. By using a qualitative approach involving archival research of the Constitutional Court’s sessions on disputed results in Indonesia’s 2019 elections, this article finds the Constitutional Court has been able to prevent rapid democratic backsliding and even a reversion to authoritarianism, by ensuring competitiveness, participation and accountability in elections.